Pembuatan Pupuk Organik Cair (POC) Dari Nasi Sisa Bagi Ibu-Ibu Di Dusun IV B Karang Sari, Jatimulyo, Lampung Selatan - Yulianty; Endang Nurcahyani; Emantis Rosa; Sri Wahyuningsih (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Leftover rice is one type of organic waste that can be recycled. However, people generally throw leftover rice into the trash. If this waste is left unattended, it will cause an unpleasant odor and can pollute the environment. One solution to overcome this problem is to create liquid local microorganisms that can be used as liquid organic fertilizer (POC). This organic fertilizer can enhance plant growth. Therefore, it needs to be developed as an environmentally friendly organic fertilizer. An activity that can be carried out is to conduct training on making POC from leftover rice for women in Dusun IVB Karang Sari, Jatimulyo District, South Lampung Regency, Lampung Province. This community service activity aims to increase knowledge and skills in making Liquid Organic Fertilizer from leftover rice. The results of this community service activity show an increase in knowledge and skills, as seen from the pre-test results of 70.81 and the post-test results of 91.35. There was an increase of 20.54 points. The sustainability of this activity is the wpmen in Dusun IV B Karang Sari can make Liquid Organic Fertilizer from leftover rice and use it for their plants.